2007
DOI: 10.1021/bi701509n
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Heme-Binding Sites in the Cytoplasmic Heme-Trafficking Protein PhuS from Pseudomonas aeruginosa and Their Relevance to Function

Abstract: PhuS is a cytoplasmic, 39 kDa heme-binding protein from Pseudomonas aeruginosa. It has previously been shown to transfer heme to its cognate heme oxygenase. It is expressed from the phu operon, which encodes a group of proteins known to actively internalize and transport heme from host organisms. This study combines the spectral resolution of resonance Raman spectroscopy with site-directed mutagenesis to identify and characterize the heme-bound states of holo-PhuS. This combined approach has identified a site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 32 publications
6
40
0
Order By: Relevance
“…This is consistent with previous in vitro reports that PhuS functions to traffic heme to the iron regulated HO (10,11,47). The observation of the premature production of pyocyanin in the phuS mutants and the confirmation that heme can override suppression of the phu operon by Fur, indicates that there is a separate and distinct heme-dependent regulation of the phu operon.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous in vitro reports that PhuS functions to traffic heme to the iron regulated HO (10,11,47). The observation of the premature production of pyocyanin in the phuS mutants and the confirmation that heme can override suppression of the phu operon by Fur, indicates that there is a separate and distinct heme-dependent regulation of the phu operon.…”
Section: Discussionsupporting
confidence: 92%
“…1A). These data taken together are consistent with our previous in vitro studies, which have characterized PhuS as a heme-trafficking protein to the iron-regulated HO for degradation and release of iron (10,11,47). Interestingly, the phuS mutant in contrast to the parent strain or the mutants carrying the hemO gene deletion began to produce a blue-green pigment (supplemental Fig.…”
Section: Phus Is Required For Efficient Heme Utilization In Psupporting
confidence: 91%
“…The heme trafficking protein CcmE from E. coli, which trafficks heme to periplasmic cytochrome enzymes, is covalently linked to heme at His130 (30). Heme is coordinated to the PhuS protein at the conserved His209 residue or the nonconserved His212 residue (31). Therefore, given the absence of a crystal structure or a clear hemin-binding motif, the conserved tyrosine (Y57), cysteine (C89), and histidine (H46) residues in Cj1386 were mutated to identify residues important for hemin ligand binding in Cj1386.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that additional amino acids compensate for hemin binding in the absence of Y57 to produce the 6-coordinate peak. Indeed, heme coordination to PhuS in P. aeruginosa still can be achieved in a His209 mutant by compensation by an alternative heme coordinating residue, His212 (31). From the multiple-sequence alignment of Cj1386, a less conserved tyrosine residue (Y61), which is in close proximity to Y57, could play a role as an alternative hemin-coordinating residue.…”
Section: Discussionmentioning
confidence: 99%
“…Once internalized heme is sequestered by the cytoplasmic heme-binding protein PhuS. In a series of in vitro studies we have shown that the cytoplasmic heme-binding protein PhuS forms a specific protein complex with the ironregulated heme oxygenase, HemO (7)(8)(9). Heme is transferred to HemO for further degradation with the release of iron, CO, and biliverdin IX (BVIX) ␦-and ␤-isomers (10,11).…”
mentioning
confidence: 99%